1999
DOI: 10.1099/0022-1317-80-2-371
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Dobrava hantavirus carried by the striped field mouse (Apodemus agrarius) in Estonia.

Abstract: Dobrava hantavirus (DOB) was isolated from the striped field mouse (Apodemus agrarius) trapped on Saaremaa Island, Estonia, and its genetic and antigenic characteristics were subsequently analysed. Phylogenetic analysis showed that the Estonian DOB strain, together with several wild strains carried by Apodemus agrarius, forms a well-supported lineage within the DOB clade. The topography of the trees calculated for the S, M and L nucleotide sequences of the Estonian DOB suggests a similar evolutionary history f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 38 publications
(26 reference statements)
2
86
1
1
Order By: Relevance
“…3). showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3). showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The rodents analysed in this survey were captured using live traps (Ugglan special, Allan Ahlgren AB, Marieholm, Sweden) as part of studies investigating diseases of small mammals , Nemirov et al 1999, Soveri et al 2000. The study areas, rodent species and number of individuals examined are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Another genetic lineage of DOBV was found in the A. agrarius species on the Saaremaa island of Estonia, northeastern Europe; the Saaremaa virus has been established in cell culture (18). Later, these researchers postulated that Saaremaa virus should represent its own virus species separately from DOBV (19).…”
Section: Hemorrhagic Fever With Renal Syndrome Caused By 2 Lineages Omentioning
confidence: 99%